Evaluating ecosystem-based management alternatives for the Puget Sound, U.S.A. social-ecological system using qualitative watershed models - Magel, Caitlin L.; Francis, Tessa B. (Frontiers in Marine Science, 2022)
Population growth and the associated transformation of landscapes is a major management challenge for coastal ecosystems. Coastal conservation and management should be guided by social, cultural, economic, and ecological objectives, but integrative decision support tools appropriate for complex ecosystems remain underutilized. Evaluating alternative policies for objectives that span the interconnected terrestrial, freshwater, and estuarine habitats along coastlines is limited by the lack of appropriate quantitative tools and available data. We employed qualitative network models (QNMs) to evaluate multi-benefit outcomes of potential management interventions to address population growth and development using a case study of Puget Sound – a large, urbanized fjord-type estuary in Washington, U.S.A. With input from regional scientists and stakeholders, we developed a base conceptual model of the links among human stressors and ecosystem components across the terrestrial-freshwater-estuarine gradient of a generalized Puget Sound watershed. We simulated scenarios representing alternative strategies for accommodating human population growth, namely new development outside of urban centers versus redevelopment (densification) within urban centers, and characterized the responses of multiple recovery objectives and ecosystem stressors for each scenario. Of the urban redevelopment scenarios, reducing stormwater runoff and increasing green infrastructure provided the most favorable outcomes. On rural lands, limiting new development to existing transportation corridors and iincreasing floodplain and riparian habitat extent concomitant with new development produced similar outcomes. Moderate levels of coordinated interventions on both urban and rural lands had favorable outcomes for more ecosystem objectives compared to either moderate intervention applied separately. This study demonstrates the value of qualitative tools for cross-habitat evaluations of possible futures in complex ecosystem-based management systems.